1989
DOI: 10.1159/000110170
|View full text |Cite
|
Sign up to set email alerts
|

Transient Ischemic Attacks in the Community: Occurrence and Clinical Characteristics

Abstract: A simple self-administered questionnaire was mailed to a population sample of 8,626 (40–65 years old) to identify transient ischemic attacks (TIAs) that occurred in the previous 12 months. This study was conducted in a well-defined, medically controlled geographic area. 75.4% of the questionnaires were returned. The procedure identified 52 TIA cases (43 definite and 9 uncertain). The 12-month period prevalence for TIAs was 6.6 per 1,000 (95% confidence limits of 4.8–8.9) among the respondents. The annual incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Furthermore, the Lemesle/Madinier/Menassa/Billiar/ Becker/Giroud proportion of first-ever TIAs in the vertebrobasilar distribution in our city (19%) is similar to that found previously [4,20]. However, some postal questionnaire-based studies [10,16,17,19] have reported higher rates of vertebrobasilar TIA.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the Lemesle/Madinier/Menassa/Billiar/ Becker/Giroud proportion of first-ever TIAs in the vertebrobasilar distribution in our city (19%) is similar to that found previously [4,20]. However, some postal questionnaire-based studies [10,16,17,19] have reported higher rates of vertebrobasilar TIA.…”
Section: Discussionsupporting
confidence: 88%
“…Other European studies based on different methodology such as postal questionnaires [17] or on door-to-door survey [22] estimate higher incidence of first-ever TIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Several patients with TIA do not seek medical advice and several others are not hospitalized. [23][24][25] To overcome these shortcomings, we used multiple sources of case finding (hospitals, outpatient clinics, GP, death certificates), and we provide a rigorous and standardized definition of incident TIA to include cases at an early and uniform point of the natural history of the disease. 18,26 TIA and stroke cases were assessed simultaneously to reduce the possibility of a misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective registry-type studies with stringent inclusion criteria tend to report lower incidences, rang-ing from 50 per 100 000 19 to 80 per 100 000, 20,21 whereas studies relying on survey methodologies report higher incidence rates, ranging from 280 per 100 000 22 to 310 per 100 000. 23 It may be that the true incidence of TIA is likely to lie somewhere between the high incidence reported by subjects in the community when directly questioned and the low incidence reported by prospective observational studies.…”
Section: Discussionmentioning
confidence: 99%